Case Report: Bilateral Sensorineural Hearing Loss - Faradhifa Karima Ardianti; Fivien Fedriani (CV. Jasa Sukses Abadi, 2026)
Sensorineural hearing loss (SNHL) is a hearing disorder caused by damage to the cochlea, auditory nerve, or central auditory pathways connecting the ear to the brain. It is the most common type of hearing impairment, affecting more than 5% of the global population, and its prevalence continues to increase with aging. The etiology of SNHL is multifactorial, including age-related degeneration, noise exposure, infection, vascular disorders, and autoimmune diseases. This case report describes a 63-year-old man with a history of Autoimmune Hemolytic Anemia (AIHA) who developed sudden bilateral hearing loss after receiving a transfusion of two units of blood. The hearing loss was preceded by tinnitus and was occasionally accompanied by vertigo without other associated symptoms. Ear, nose, and throat examinations were unremarkable. The whisper test indicated severe hearing loss, while tuning fork tests could not be performed because the patient was unable to perceive the sound. Pure-tone audiometry confirmed severe bilateral sensorineural hearing loss, and the patient was advised to use hearing aids. The diagnosis was established through comprehensive history taking, physical examination, hearing assessment, and audiometric evaluation. The underlying pathophysiology was considered to involve age-related cochlear degeneration aggravated by systemic autoimmune inflammation. Prognosis depends on the severity and underlying etiology of hearing loss. This case highlights the importance of comprehensive clinical evaluation, audiometry, and appropriate management to determine disease severity, improve communication, prevent complications, and optimize the patient's quality of life.